Awareness study of Pharmacovigilance among the health care professionals (nursing staff) at tertiary care hospital, Solapur, Maharashtra, India - Patil, Amruta Pasgonda; Shirure, Prashant A.; Khobragade, Rasika S. (International Journal of Research in Medical Sciences, 2017)
Background: Early detection of adverse drug reaction is one step towards the prevention of ADRs. Foundation of Pharmacovigilance is spontaneous reporting which is minimal in India. Among the all health care professionals, nurses are caregivers at bedside. Improvement in knowledge and practice of adverse drug reaction reporting among nurses will definitely increases spontaneous reporting. In this study, knowledge, attitude and practice of nursing staff about pharmacovigilance was evaluated. Methods: It was prospective, cross-sectional, observational, questionnaire-based study among the nurses of the tertiary care hospital Solapur. A questionnaire evaluating knowledge, attitude and practice was distributed among nursing staff and filled questionnaire were collected back and analyzed by microsoft excel 2013. Results: Response rate of our study was 44.88%. 38.61% doctors were knowing meaning of pharmacovigilance while 61.38% participants knew that all drugs available in market are not safe. Taking proper medication history before prescribing drugs was considered important by 92.57% participants. 79.70% participants were aware about Pharmacovigilance program of India. 64.35% doctors answered correctly to elements which are mandatory to record. Only 24.75% participants were knowing the basis that pharmcovigilance provides for. Conclusions: Nursing staff of tertiary care hospital, Solapur had very appreciable and positive attitude towards pharmacovigilance but there is a need for improvement in knowledge and practice of ADR reporting.